Teens’ Vision of an Ideal Library Space: Insights from a Small Rural Public Library in the United States - Li, Xiaofeng; Ha, YooJin; Aristeguieta, Simon (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – This study delves into the perspectives of teenagers regarding their desired teen space within a small rural public library in the United States.Methods – To capture the richness of their thoughts, a visual data collection method was employed, wherein 27 8th-grade participants engaged in a drawing activity during an art class at a local middle school. Two additional teens were recruited for individual semi-structured interviews.Results – Through this creative exercise, the study unveiled the various library activities, amenities, books, and visual designs that resonated with the teens, as they envisioned their ideal teen space.Conclusion – The study’s findings hold practical implications for librarians working with this population, offering valuable insights to enhance and optimize teen services at the library. By aligning the library’s offerings with the desires of the young patrons, the potential for a thriving and engaging teen community within the library is enhanced.